2021
DOI: 10.1021/acsami.1c08363
|View full text |Cite
|
Sign up to set email alerts
|

Double Active Sites in Co–Nx–C@Co Electrocatalysts for Simultaneous Production of Hydrogen and Carbon Monoxide

Abstract: The hydrogen evolution reaction (HER) by electrocatalytic water splitting is a prospective and economical route. However, the approach is severely hindered by the sluggish anodic OER, poor reactivity of electrocatalysts, and low-value-added byproducts at the anode. Herein, formaldehyde was added as an anode sacrificial agent, and a bifunctional Co–N x –C@Co catalyst containing abundant Co–N4 sites and Co nanoparticles was successfully fabricated and evaluated as both a cathodic and an anodic material for the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…As can be seen from Figure S13, the SS-CNRs had a comparatively lower electrochemical surface area compared with CNRs and CNPs, whereas the SS-CNRs possessed the highest kinetics for electrocatalytic dechlorination of 1,2-DCA. Thus, it may be inferred that the high electrocatalytic performance of SS-CNRs benefits from their intrinsic catalytic activity rather than the electrochemical surface area. , Moreover, compared with the previous works (Tables S4 and S5), ,, the FE ethylene and production rate at −2.55 and −2.75 V in this work are relatively higher than previously reported ones, and this has proven that the as-synthesized sea-urchin-like carbon nanosphere catalyst exhibits outstanding electrocatalytic dechlorination performance of 1,2-DCA. Based on the different outcomes for the similar electrocatalytic reaction, it may be confirmed that the unique sea-urchin-like spherical superstructure has played an indispensable role.…”
Section: Resultssupporting
confidence: 42%
“…As can be seen from Figure S13, the SS-CNRs had a comparatively lower electrochemical surface area compared with CNRs and CNPs, whereas the SS-CNRs possessed the highest kinetics for electrocatalytic dechlorination of 1,2-DCA. Thus, it may be inferred that the high electrocatalytic performance of SS-CNRs benefits from their intrinsic catalytic activity rather than the electrochemical surface area. , Moreover, compared with the previous works (Tables S4 and S5), ,, the FE ethylene and production rate at −2.55 and −2.75 V in this work are relatively higher than previously reported ones, and this has proven that the as-synthesized sea-urchin-like carbon nanosphere catalyst exhibits outstanding electrocatalytic dechlorination performance of 1,2-DCA. Based on the different outcomes for the similar electrocatalytic reaction, it may be confirmed that the unique sea-urchin-like spherical superstructure has played an indispensable role.…”
Section: Resultssupporting
confidence: 42%
“…Taking NCO 4−β /C 1 as an example, the value of I D / I G is 0.4, which indicated the successful coating of carbon on NCO 4−β . This result could be profitable to the electrocatalytic dechlorination of DCM . To further verify the functional groups contained in NCO 4−β and NCO 4−β /C x ( x = 0.5, 1, 2, 3), the Fourier transform infrared spectrare revealed in Figure d.…”
Section: Resultsmentioning
confidence: 86%
“…33 This result could be profitable to the electrocatalytic dechlorination of DCM. 34 To further verify the functional groups contained in NCO 4−β and NCO 4−β /C x (x = 0.5, 1, 2, 3), the Fourier transform infrared spectrare revealed in Figure 4d. Among them, the large peak around 1628 cm −1 was due to the stretching vibration of H 2 O molecules.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Formaldehyde (HCHO) is the most reductive aldehyde and is expected to achieve ultra-low aldehyde oxidation via the EOD pathway. [31][32][33] In addition, HCHO has been reported to reduce Cu 2+ to metallic Cu when complexed by EDTA or tartrate and can rapidly reduce Cu(OH) 2 to form Cu 2 O. 34,35 The interaction between HCHO and Cu-based catalysts could satisfy the needs for a special anodic aldehyde oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%